2016
DOI: 10.3390/ijms17020185
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Challenges for Use of Cell-Penetrating Peptides as Delivery Vectors for Peptide and Protein Cargos

Abstract: The hydrophilic nature of peptides and proteins renders them impermeable to cell membranes. Thus, in order to successfully deliver peptide and protein-based therapeutics across the plasma membrane or epithelial and endothelial barriers, a permeation enhancing strategy must be employed. Cell-penetrating peptides (CPPs) constitute a promising tool and have shown applications for peptide and protein delivery into cells as well as across various epithelia and the blood-brain barrier (BBB). CPP-mediated delivery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(192 citation statements)
references
References 107 publications
4
182
0
Order By: Relevance
“…22,23 To meet these drawbacks, numerous peptide modifications have been explored. In analogy to cell penetrating peptides (CPP), 24,25 cellular uptake can be improved by incorporation of positively charged amino acids. 17,26 Proteolytic stability can be increased by incorporation of non-natural building blocks including N-methylated, 27,28 β- [29][30][31] or D-amino acids 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 To meet these drawbacks, numerous peptide modifications have been explored. In analogy to cell penetrating peptides (CPP), 24,25 cellular uptake can be improved by incorporation of positively charged amino acids. 17,26 Proteolytic stability can be increased by incorporation of non-natural building blocks including N-methylated, 27,28 β- [29][30][31] or D-amino acids 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…We selected SynB, Hst5, and MPG as our CPPs, because they were each previously shown to translocate cargo into cells [Alhakamy et al, 2013;Copolovici et al, 2014;Du et al, 2017;Ilsen and Onsan, 1998;Kristensen et al, 2016;Morris et al, 2008;Shin et al, 2014;Temsamani and Laruelle, 2010;Yu et al, 2015] and use varied mechanisms for translocation [Drin et al, 2003;Gong et al, 2018;Gong and Karlsson, 2017;Rajarao et al, 2002Rajarao et al, , 2003Tan et al, 1996;Temsamani and Laruelle, 2010]. SynB (RGGRLSYSRRRFSTSTGR) is from the antimicrobial peptide protegrin 1, an 18-amino acid peptide initially isolated from porcine leukocytes [Temsamani and Laruelle, 2010].…”
Section: Resultsmentioning
confidence: 99%
“…Tarp is usually translocated into the host cell cytoplasm via the T3SS but the initial in silico structural analysis indicated that it was not cell permeable (41). To facilitate the translocation of the peptide into host cells, the peptide was conjugated to the C-terminus of HIV’s trans-activator of transcription (TAT) peptide known to translocate conjugated cargos into mammalian cells (42). A non-functional TAT-fused peptide was also designed using a randomly scrambled peptide generated from the proline-rich amino acid 618–654 using PepControls web server tool (43).…”
Section: Methodsmentioning
confidence: 99%